Does Bubble Still Exist after COVID-19? Evidence from Hong Kong Housing Market - Tang, Edward Chi-Ho (Bubbles and Behavioral Finance, 2024)
Hong Kong housing is commonly known as one of the most unaffordable housing in the world. The housing bubble is formed due to low interest rates, a limited amount of housing supply and speculation. Even though the Hong Kong government launched countercyclical housing policies to stabilize the market, the inflating housing bubble was unstoppable. The situation continued until the emergence of COVID-19, which brought a huge negative shock to the market. This paper revisits the housing bubble by using the right-tailed ADF test and provides useful policy recommendations at the end.